Demand for petrol and tobacco in Ireland - Geary, P.T. (Economic & Social Studies, 1973)
In a recent issue of this Review, W. K. O'Riordan presented estimates of the demand function for petrol in Ireland. His paper raises a number of points which call for comment - some of these points are also relevant to an earlier study by O'Riordan of the demand for tobacco.
Keywords: Petrol; Tobaco; Ireland